Managing Student Development through Mindfulness Education: An Experimental Study on Meditation Retreat, Mindful Living Education, and Compassion Effectiveness - Burmansah, Burmansah; Putra Pembangunan, Heldy Ramadhan; Suryanadi, Juni; Susanto, Susanto; Tu, Chan Phap (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The growing interest in mindfulness-based education highlights the need for approaches that integrate cultural and spiritual traditions to support students’ holistic development. This study aims to examine the effectiveness of a Buddhist meditation retreat combined with mindful living education in enhancing mindfulness and compassion among students in Palembang City, Indonesia. Using a quasi-experimental design with pre-test and post-test control groups, the research selected 120 students from a population of 170 through the Slovin formula. Participants were divided into experimental and control groups across junior and senior high schools. The experimental group attended a structured retreat that combined traditional Buddhist practices, such as mindful breathing, insight meditation, and loving-kindness meditation, with mindful living activities inspired by Zen Master Thich Nhat Hanh’s teachings, including cultivating awareness in daily routines, deep listening, and compassionate communication. Data were collected using researcher-developed questionnaires. Results showed that the experimental group experienced significant improvements in mindfulness and compassion, whereas the control group displayed minimal changes. Baseline equivalence was established, and post-test comparisons consistently favored the experimental group. These findings suggest that culturally grounded mindfulness programs can foster emotional awareness and prosocial behavior in youth. Practically, the study encourages educational institutions to adopt mindfulness interventions and recommends further research with broader populations, validated instruments, and long-term evaluation.